Being physically active minimizes the effects of leg muscle fatigue on obstacle negotiation in people with Parkinson's disease - Santos, Paulo Cezar Rocha dos [UNESP]; Barbieri, Fabio Augusto [UNESP]; Orcioli-Silva, Diego [UNESP]; Beretta, Victor Spiandor [UNESP]; Hortobágyi, Tibor; Gobbi, Lilian Teresa Bucken [UNESP] (Elsevier, 2021)
It is challenging for people with Parkinson's disease (PwPD) to adjust their gait to perturbations, including fatigue. Obstacle negotiation increases the risk of tripping and falling in PD. Being physically active can improve gait control and the ability to negotiate obstacles while walking under fatigue state. We thus determined the effects of Parkinson's disease, fatigue, and level of physical activity on gait during the approach to and crossing an obstacle during gait. Forty participants were stratified to people with Parkinson's disease active and inactive, and control individuals active and inactive. Participants walked on an 8 m walkway and stepped over an obstacle placed at the middle (4 m). They performed three trials before and after repeated sit-to-stand (rSTS)-induced fatigue state. Maximum voluntary force was assessed before and after rSTS. We measured the length, width, duration, and velocity of the approach (stride before obstacle) and crossing (step over the obstacle) phases and the leading and trailing placements and clearance during crossing phase. Fatigue trait was determined by multidimensional fatigue inventory. Before rSTS, people with Parkinson's disease inactive vs. other subgroups approached the obstacle using 18–28% shorter, wider and slower steps and crossed the obstacle slower (all p < 0.04). After rSTS, people with Parkinson's disease inactive increased (23–34%) stride length and velocity and decreased (-21%) the step width (p < 0.01). People with Parkinson's disease approached the obstacle similarly to control individuals. Physical activity minimizes Parkinson's disease-typical gait impairments during obstacle negotiation and affords a protective effect against fatigue-effects on obstacle negotiation.
Keywords: Exercise; Fatigability; Obstacle avoidance; Parkinson's disease; Physical activity